This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You could make the differentiation a little easier by making the substitution t = 1/x and changing the limit to t -> 0
1.- x → ∞ lim ( x 2 + x − x ) = x → ∞ lim ( x 2 + x − x ) ⋅ x 2 + x + x x 2 + x + x = = x → ∞ lim x 2 + x + x x 2 + x − x 2 = x → ∞ lim x 2 + x + x x = Now, let's divide numerator and denominator by x = x → ∞ lim 1 + x 1 + 1 1 = 2 1
I have an intriguing way of solving this which i kinda discovered. I solved it by A.M.- G.M. inequality. x + ( 1 / 2 ) ≥ x ( x + 1 )
As x tends to ∞, x ≈ x+1. Hence we can use the upper limit. Hence, the term reduces to x+(1/2)-x = 1/2. ( I doubt this step too but i leave it to the masters to guide me) This solution makes me wonder how should we deal with infinities O.o but one thing is for sure, x tends to infinity but not infinity ;)
Rationalise and then take 'x' common in numerator as well as denominator
Yes did the same!
You can show this with binomial expansion for the root: sqrt(x^2+x)=x*sqrt(1+1/x) is approx. x(1+1/2x) as 1/x->0. So, you get x+1/2-x=1/2.
x → ∞ lim x 2 + x − x = x → ∞ lim ( x + 2 1 ) 2 − 4 1 − x = x → ∞ lim ( x + 2 1 ) 2 − x = x → ∞ lim ( x + 2 1 ) − x = 2 1
Problem Loading...
Note Loading...
Set Loading...
x → ∞ lim x 2 + x − x
⇒ x → ∞ lim x × ( 1 + x 1 − 1 )
⇒ x → ∞ lim x 1 ( 1 + x 1 − 1 ) ( 0 0 f o r m )
Applying L'Hopital's Rule :
⇒ x → ∞ lim x 2 − 1 ( 2 1 + x 1 x 2 − 1 )
⇒ x → ∞ lim 2 1 + x 1 1
⇒ 2 1 + 0 1
⇒ 2 1